An implicit compact finite difference method for the fractional reaction-subdiffusion equation - Sepehrian, Behnam; Jabbari, Mahboobeh (International Journal of Applied Mathematical Research, 2014)
In this article, a high order implicit compact difference method for the fractional reaction-subdiffusion equation is presented. The difference scheme is unconditionally stable and the truncation error is of first order in time and forth order in space. A numerical example is included to demonstrate the validity of theoretical results and efficiency of the scheme.